2014
DOI: 10.1088/0031-9155/59/5/1189
|View full text |Cite
|
Sign up to set email alerts
|

A multi-source inverse-geometry CT system: initial results with an 8 spot x-ray source array

Abstract: We present initial experimental results of a rotating-gantry multi-source inverse-geometry CT (MS-IGCT) system. The MS-IGCT system was built with a single module of 2×4 x-ray sources and a 2D detector array. It produced a 75 mm in-plane field-of-view (FOV) with 160 mm axial coverage in a single gantry rotation. To evaluate system performance, a 2.5 inch diameter uniform PMMA cylinder phantom, a 200 μm diameter tungsten wire, and a euthanized rat were scanned. Each scan acquired 125 views per source and the gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Each module consists of 64 by 16 cells of about 1.1 mm × 1.0 mm each. 12 modules are tiled in z producing a total sensitive area of about 70 mm in the x direction and 192 mm in the z direction [4,5]. Figure 3 shows a picture of the integrated MS-IGCT gantry.…”
Section: System Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Each module consists of 64 by 16 cells of about 1.1 mm × 1.0 mm each. 12 modules are tiled in z producing a total sensitive area of about 70 mm in the x direction and 192 mm in the z direction [4,5]. Figure 3 shows a picture of the integrated MS-IGCT gantry.…”
Section: System Overviewmentioning
confidence: 99%
“…We only modeled Poisson-distributed photon noise; this should also be relevant to other random noise in the imaging system. For image reconstruction, corrected projection data were rebinned into a full fan beam geometry [5], and then a direct fan beam reconstruction algorithm was used. As a reference, images were reconstructed from projection data without source intensity fluctuation.…”
Section: Computer Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To substantially increase the scanning field of view (FOV), multieye IGCT was proposed employing additional detector arrays, in which each detector sees only a portion of the FOV . In addition, a prototype has been developed and evaluated with gantry‐based multisource IGCT . It is reported that the temporal resolution of IGCT is still limited by the gantry rotation speed, which is largely determined by electrical and mechanical designs and implementations.…”
Section: Introductionmentioning
confidence: 99%
“…We previously presented the development of multisource reconstruction methods [12][13][14][15][16][17][18][19][20] and calibration methods. [21][22][23][24] Several progress updates on the system development and initial results were published in Refs. [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%